Fucoidan derived from Sargassum ilicifolium affects growth and hemato-immunological parameters and antioxidant defense in Oscar (Astronotus ocellatus) - Khanzadeh, Majid; Hoseinifar, Seyed Hossein; Zargari, Ashkan; Tabibi, Hamidreza; Van Doan, Hien; Rabetimarghezar, Nastaran (Frontiers in Marine Science, 2024)
Fucoidan (Fuc) is a sulfated polysaccharide derived from brown algae and has various biological activities such as immune modulator, growth enhancer, antioxidant and bactericidal. However, there is no information about the effect of fucoidan on ornamental fish. This study investigated the effect of fucoidan from brown algae Sargassum ilicifolium on growth parameters, immunity, and biochemical, antioxidant, and bactericidal activity of serum in Oscar. Fish weighing 49.75 ± 0.96 g were fed fucoidan derived from S. ilicifolium algae at four levels (0%, 0.5%, 1%, and 2%) for 50 days. After 50 days of feeding with fucoidan, there was no significant increase in blood parameters except WBCs (Fuc 2%) compared to the control group (p < 0.05). The weight gain (WG), feed conversion ratio (FCR), and specific growth rate (SGR) after feeding with fucoidan had a significant increase compared to the control group (p < 0.05). Serum biochemical activity such as total protein (Tp) and globulin (Glb) in the groups fed with fucoidan had a significant increase compared to the control group (p < 0.05), but no significant difference was observed in the serum albumin (Alb) activity compared to the control group (p > 0.05). Antioxidant activity of serum, such as SOD and CAT, after feeding with fucoidan, had a significant increase compared to the control group (p < 0.05). In addition, immune parameters such as lysozyme and total complement in groups containing fucoidan significantly increased compared to the control group (p < 0.05). A significant increase was observed in NBT and serum bactericidal activity against Aeromonas hydrophila in the group containing Fuc 2% compared to the control group (p < 0.05). A significant increase was observed in total skin carotenoids in the groups containing 1% and 2% fucoidan compared to the control group (p < 0.05). Overall, it can be concluded that fucoidan of S. ilicifolium algae can increase growth and immune parameters. In addition, fucoidan derived from S. ilicifolium algae could increase skin pigmentation, antioxidant enzyme activity, and bactericidal activity against A. hydrophila.